"I felt so old this morning." Short-term variations in subjective age and the role of trait subjective age: evidence from the ILSE/EMIL ecological momentary assessment data - Kornadt, Anna Elena; Weiss, David; Gerstorf, Denis; Kunzmann, Ute; Lücke, Anna J.; Schilling, Oliver; Katzorreck, Martin; Siebert, Jelena Sophie; Wahl, Hans-Werner (Psychology and aging, 2021)
Subjective age, how old people feel compared to their chronological age, is a central indicator of age identity and highly predictive for developmental outcomes. While mostly used as a trait-like concept in previous research, recent studies employing experimental designs and daily assessments suggest that subjective age can vary after experimental manipulations or between days. However, less is known about whether subjective age varies over even shorter time frames such as within moments on a given day, how such short-term variability differs by age and its association with trait subjective age. We examined these questions with data obtained from 123 young-old (M-age = 67.19 years) and 47 old-old adults (M-age = 86.59 years) who reported their momentary subjective age six times a day over 7 consecutive days as they were going about their everyday lives. Participants felt younger on a large majority of occasions, and 25% of the total variability in subjective age could be attributed to within-person variation. Within-person variability in subjective age amounted to an average of about 3 years from one moment to the next and did not differ between age groups. However, those with younger trait subjective ages exhibited larger moment-to-moment variation. Our findings extend the literature on subjective age by showing that how old people feel can vary on a momentary basis and that state and trait components of subjective age are related. Further research should investigate the contextual predictors of variability in subjective age and the links between trait and state concepts and developmental outcomes.